Красный террор в России, 1918-1923 - Мельгунов Сергей Петрович (Белая Россия, 2006)
Экземпляры: аб. (2020) / Инвентарный номер: 56285 / Цена: / Сис.шифр: 63.3(2)61 / Авт.знак: М 48 / ГРНТИ: 03.23.55 / ББК: 63.3(2)61